2012
DOI: 10.1017/s1751731112000730
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α-tocopherol supplementation on trans-18:1 and conjugated linoleic acid profiles in beef from steers fed a barley-based diet

Abstract: The current study was conducted to determine the effect of different α-tocopherol (vitamin E) inclusion levels ontrans(t)-18:1 and conjugated linoleic acid (CLA) profiles in subcutaneous and intramuscular fat of steers fed a barley-based diet. Fifty-six feedlot steers were offered a barley-based finisher diet (73% steam rolled barley, 22% barley silage and 5% supplement as-fed basis) with four levels of supplementarydl-α-tocophery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
3
16
1
Order By: Relevance
“…In support of this assertion, supplementing high-grain diets with vitamin E was shown to reduce t10-18:1 deposition, and maintain or increase VA proportions in beef Mapiye et al, 2012b). Similarly, feeding grain-based diets, and extracts or leaf-meals rich in secondary compounds such as condensed tannins (Jerónimo et al, 2010a;Rana, Tyagi, Hossain, & Tyagi, 2012;Vasta & Luciano, 2011), polyphenol oxidase (Mapiye et al, 2013a) and saponins (Brogna et al, 2014;Lourenço et al, 2010;Vasta & Luciano, 2011) have been reported to increase total and individual t-18:1 isomers, especially VA in ruminant meat, thus improving the VA to t10-18:1 ratio.…”
Section: Addition Of Antioxidantsmentioning
confidence: 85%
“…In support of this assertion, supplementing high-grain diets with vitamin E was shown to reduce t10-18:1 deposition, and maintain or increase VA proportions in beef Mapiye et al, 2012b). Similarly, feeding grain-based diets, and extracts or leaf-meals rich in secondary compounds such as condensed tannins (Jerónimo et al, 2010a;Rana, Tyagi, Hossain, & Tyagi, 2012;Vasta & Luciano, 2011), polyphenol oxidase (Mapiye et al, 2013a) and saponins (Brogna et al, 2014;Lourenço et al, 2010;Vasta & Luciano, 2011) have been reported to increase total and individual t-18:1 isomers, especially VA in ruminant meat, thus improving the VA to t10-18:1 ratio.…”
Section: Addition Of Antioxidantsmentioning
confidence: 85%
“…Palmitic acid C16:0 constituted the second major fatty acid detected [20][21][22][23][24][25][26][27][28] , followed by stearic acid C18:0, 10-19 , palmitoleic acid C16:1 cis, [2][3][4][5] , myristic acid C14:0, 2-4 and linoleic acid C18:2 n6, 2-10 . In the storage fat, the saturated fatty acids SFA were present in significantly p 0.05 greater amounts in calf and young bull 46.76 and 47.62…”
Section: Fatty Acid Composition Of By-productsmentioning
confidence: 99%
“…Bovines are ruminants and the rumen microflora conduct a hydrogenation process of unsaturated fatty acids making them saturated, increasing the total SFA amount 27 .…”
Section: Fatty Acid Composition Of By-productsmentioning
confidence: 99%
“…Elucidation of these effects requires considerable analytical effort for the determination and quantification of all single trans-18:1 fatty acid isomers in beef. Vaccenic acid (VA, is the most abundant trans-18:1 fatty acid isomer in beef from pasture-based fed cattle; however barleybased diets of British × Continental crossbred steers result in higher concentrations of 18:1trans-10 compared to VA and replaced VA as the major isomer in beef muscle (Mapiye et al, 2012). Also the muscle from feedlot-fed bulls, intensive indoor-fed Limousin bulls and Normand cull cows had higher 18:1trans-10 compared to VA contents (Alfaia et al, 2009;Bauchart et al, 2010;Kraft, Kramer, Schoene, Chambers, & Jahreis, 2008).…”
Section: Breedmentioning
confidence: 99%